Management of Advanced Therapies in Parkinson's Disease Patients in Times of Humanitarian Crisis: The COVID‐19 Experience. Issue 4 (4th May 2020) - Fasano, Alfonso; Antonini, Angelo; Katzenschlager, Regina; Krack, Paul; Odin, Per; Evans, Andrew H.; Foltynie, Thomas; Volkmann, Jens; Merello, Marcelo
ABSTRACT: Background: Although the COVID‐19 pandemic is affecting a relatively small proportion of the global population, its effects have already reached everyone. The pandemic has the potential to differentially disadvantage chronically ill patients, including those with Parkinson's disease (PD). The first health care reaction has been to limit access to clinics and neurology wards to preserve fragile patients with PD from being infected. In some regions, the shortage of medical staff has also forced movement disorders neurologists to provide care for patients with COVID‐19. Objective: To share the experience of various movement disorder neurologists operating in different world regions and provide a common approach to patients with PD, with a focus on those already on advanced therapies, which may serve as guidance in the current pandemic and for emergency situations that we may face in the future. Conclusion: Most of us were unprepared to deal with this condition given that in many health care systems, telemedicine has been only marginally available or only limited to email or telephone contacts. In addition, to ensure sufficient access to intensive care unit beds, most elective procedures (including deep brain stimulation or the initiation of infusion therapies) have been postponed. We all hope there will soon be a time when we will return to more regular hospital schedules. However, we should consider this crisis as an opportunity to change our approach and encourage our hospitals and health care systems to facilitate the remote management of chronic neurological patients, including those with advanced PD.